Updates on Cancer Treatment - Rangel, Leticia B. A.; Victor Silva, Ian (IntechOpen, 2015)
In spite of advances in the cancer research field, cancer treatment still challenges researchers and clinicians, as proven by the still impressive and increasing number of worldwide cancer-related deaths. Updates on Cancer Treatment is an attempt to integrate into a book volume various aspects of cancer treatment, compiling comprehensive reviews written by an international team of experts in the field.